2017
DOI: 10.3389/fphys.2017.00991
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sensing Receptors Mediate Local Inhibitory Reflexes Evoked by L-Phenylalanine in Guinea Pig Jejunum

Abstract: Amino acids applied to the mucosa evoke inhibitory reflexes in guinea-pig jejunum, but the receptors involved in sensory transduction are still unclear. One promising candidate is the extracellular calcium sensing receptor (CaSR), which is expressed by mucosal enteroendocrine cells and is preferentially activated by aromatic L-amino acids. We tested this by applying various amino acids to the mucosa and recording the resulting inhibitory junction potentials (IJPs) in nearby circular smooth muscle via intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Enteric mucosal cells along the entire small and large intestines express the CaSR. These include enterocytes 9 12 , neurons in the enteric nervous system (ENS) 9 , 13 and enterochromaffin (EC) cells 14 and other enteroendocrine (EE) cells (refer to a recent review by Tang et al . 15 for refs).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric mucosal cells along the entire small and large intestines express the CaSR. These include enterocytes 9 12 , neurons in the enteric nervous system (ENS) 9 , 13 and enterochromaffin (EC) cells 14 and other enteroendocrine (EE) cells (refer to a recent review by Tang et al . 15 for refs).…”
Section: Introductionmentioning
confidence: 99%
“…Since external Ca 2+ is the CaSR activator, we further examined if the CaSR is involved in this process. Different concentrations (0.1–30 μM) of NPS‐2143, a selective CaSR antagonist (Gwynne, Ly, Parry, & Bornstein, ; Zhou & Pestka, ), were added to the serosal side of the tissue. As shown in the time course of jejunal Isc (Figure c,d), Gly‐sar induced a significant increase in I sc, which was progressively smaller when the tissue was preincubated with NPS‐2143 in the serosal solution in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it has been reported that l-phenylalanine inhibits circular smooth muscles by activating the extracellular calcium-sensing receptor (CaSR) in the intestines (Gwynne et al, 2017). It can be thought that the decrease in l-phenylalanine level causes constipation from the side effects of solifenacin.…”
Section: Discussionmentioning
confidence: 99%